Criminology of Sexual Crimes (International Journal of Innovative Research in Engineering & Management, 2021)
The study of crimes is known as criminology. The field of  criminology studies why people commit crimes. This is clearly  connected to a variety of subjects, such as Criminal Justice,  which examines Police Procedure in the context of maintaining  societal control. Custody, prosecution, and the operation of the  legal system are only a few of the criminology studies.  Penology is the study of the prison system, including how  prisons operate and how probation operates thereafter.  Criminology does not attempt to determine how the world  should be, but rather seeks to comprehend what it is. The essay  discusses how a person's envy and sex drive them to commit a  crime. These offenses are sometimes committed without regard  for the repercussions. Though this type of violence does not  make national news, it fits into a trend that makes India a  dangerous place. The article uses data from the National Crime  Records Bureau (NCRB) to try to figure out how jealousy and  sexual cravings are luring more people into its trap. The word  "legal good" has the potential to reduce the number of crimes  committed.
Keywords: Criminology; Crime; Offense; Penal; Sexual